Formulation and evaluation of Yemeni potash alum as hydrophilic topical preparations against bacterial skin infections : Yemeni potash alum’s topical preparations against bacterial skin infections (Journal of Medical Science, 2022)
Skin and soft tissue infections are common. Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, and Pseudomonas aeruginosa cause most bacterial skin infections. Yemen’s alum is a natural mineral with potent antibacterial and antifungal activity. The current study aimed to verify Yemen alum’s antibacterial activity against chosen bacterial strains to formulate a valuable topical preparation. We formulated twenty-three formulations involving four non-adjusted aqueous solutions, eight adjusted pH aqueous solutions, three Oil/Water cream formulations, and eight glycerin solutions, all with different alum concentrations. After that, we evaluated the antibacterial efficacy against the selected bacterial strains. Additionally, we performed stability testing (almost six weeks) to determine the chosen preparations’ estimated shelf life (t90). Alum showed antibacterial activity against Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, and Pseudomonas aeruginosa. Finally, it was concluded that Oil/Water cream (10% alum) is viable preparation for large-scale production.